PEMANFAATAN EKSTRAK DAUN KELOR (Moringa Oleifera, Lam) SEBAGAI ANTIOKSIDAN PADA MINYAK KELAPA - Livia Fransisca Tulus; Sunarty Sunarty; Fensia A Souhoka (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2019)
This research aims to determine the compounds contained in moringa leaf methanol extract by phytochemical test, values of antioxidant activity and application for coconut oil to determine peroxide value, acid value and moisture content based on oil quality according to SNI 01-374-2013. Result of phytochemical test show that Moringa leaf methanol extract contains of alkaloid, flavonoid, saponin, tannin, terpenoid and fenolik compoundsnm. Test of antioxidant activity with DPPH and measured with a UV-Vis spectrophotometer at wavelength 517 nm. Moringa leaf methanol extract has an IC50 value of 61,625% so that it is classified as strong antioxidant. The addition of moringa leaf methanol extract 5% on coconut oil after heating at time variation 15, 30, and 40 minutes showed oil quality is better than without addition of extract with peroxide value ((1,1716, 3,8378 and 6,6043 Meq/kg), acid value (0,4700, 0,5869 and 0,7024 KOH/g), and moisture content at 1% extract concentration (0,1978, 0,1290 and 0,0896 %).